Gender Inequality in Conducting - Venske, Cassandra (My University, 2014)
In professional music performance groups, membership has become more equal between the genders; however, the percentage of female conductors does not reflect this trend. The purpose of this study was to investigate whether this inequality existed at the collegiate level in the state of Wisconsin.
Color poster with text, graphs, and images.
Keywords: Female conductors; Wisconsin universities; Posters